THE EFFECT OF SMALL GROUP DISCUSSION TEACHING METHOD TO THE READING COMPREHENSION OF NARRATIVE TEXT OF GRADE NINE STUDENTS OF SMP NEGERI 2 TAPIAN DOLOK - Veronika Febriyanti Siahaan; Sanggam Siahaan; Irene Adryani Nababan (Sindoro: Cendikia Pendidikan, 2023)
The purpose of this study was to compare the reading comprehension studies of students in class IX at SMP Negeri 2 Tapian Dolok during the academic year 2022–2023 by using the small group discussion method. With a pretest and posttest study design, quantitative research employs a quasi-experimental research methodology. Purposive sampling was used in this study to select a sample of 60 students from class IX at SMP Negeri 2 Tapian Dolok during the 2022–2023 academic year, or from two experimental classes of 30 students each. procedures for gathering data that involve testing, observations, and documentation. the information gathered on students' proficiency in reading comprehension. A reading proficiency exam was the tool utilized. The formula sample t-test was the hypothesis test that was employed. The value of t-test (3,8) > t-table (1672) in the results revealed that there were differences in the students' reading comprehension skills when using the small group discussion approach compared to the lacture-based learning traditional teaching method. When it came to reading comprehension, the small group discussion approach outperformed the standard lecture-based learning approach. With an average score of 79,5, the experimental group that underwent learning treatment through the small group discussion approach could be considered to be in the good category. The control group, on the other hand, received instruction utilizing the lecture-based learning approach and achieved an average score of 64,84.